PEMILU INDONESIA: KIBLAT NEGARA DEMOKRASI DARI BERBAGAI REFRESENTASI - Bachtiar, Farahdiba Rahma (Department of Political Science, Universitas Islam Negeri Alauddin Makassar, 2014)
Indonesia has been present and is still able to maintain itself as a democracy icon that should be followed by other countries. As one of the largest democracies in the world, Indonesia in more than ten years is continue growing and transforming with its diversity in society, the dynamics and diversity issues. Indonesia was still able to maintain its identity as a democracy. Through these facts, this paper tried to describe the political situation in Indonesia in the 2014 Presidential Election, as well as reflect further on the response and the effect of foreign parties to the democratic mechanism. What happens in the electoral process in recent months and how Indonesia continues to become an example of the success stories of various identity democracies as diverse as a multicultural country, developing countries, as well as the country with the largest Muslim adherents in the world. This paper sees the problem through the concept of elections and democracy based on the analysis of identity. Where the author tried to look outside the box of the electoral process in the domestic political analysis that has been done before. Probe Indonesia based on its identity in the international sphere as a democratic state becomes interesting when its identity was assessed by comparing it with other identities such as identity and role as a developing country and collective identity as the Southeast Asian country. The papers argue that the election process in Indonesia is not only shaped by domestic factors. Indonesia democratization maturity today can’t be separated from the support of international and Indonesian efforts in playing a role and maintain its identity as a democratic country in the international sphere. Keywords: democracy, election, identity